Inovasi Pengemasan Standing Pouch Puree Cabai Merah sebagai Upaya Pemberdayaan Masyarakat Desa Pondok Meja - Dharia Renate; Addion Nizori; Edison Edison; Endi Efran; Windika Febryanti (Universitas Perjuangan Tasikmalaya, 2026)
This community service program was conducted in Pondok Meja Village, Mestong District, Muaro Jambi Regency, aiming to enhance the skills of local women’s groups (PKK) in processing red chili into puree and packaging it using standing pouch technology. The main issue identified was the low added value of chili products due to limited knowledge of processing and packaging techniques. This program was designed to support the achievement of the Sustainable Development Goals (SDGs), particularly Goal 1 (No Poverty), Goal 5 (Gender Equality), Goal 8 (Decent Work and Economic Growth), and Goal 12 (Responsible Consumption and Production), through local food-based community empowerment. The implementation involved socialization, technical training in puree processing, standing pouch packaging practice, and evaluation through pretest and posttest. The results indicated an increase in participants’ understanding from 64.30% to 88.05%, showing an improvement of 23.75%. Moreover, participants demonstrated improved technical skills in hygienic product processing and packaging. This activity effectively transferred appropriate technology to the community and strengthened local economic independence through the development of small-scale businesses producing high-value, hygienically packaged red chili puree products.